PENINGKATAN PRODUKTIVITAS PEΜΑΝΕΝΑΝ KAYU MELALUI TEKNIK PEΜΑΝΕΝΑΝ KAYU RAMAH LINGKUNGAN: KASUS DI SATU PERUSAHAAN HUTAN RAWA GAMBUT DI KALIMANTAN BARAT - Sona Suhartana; Yuniawati (Jurnal Penelitian Hasil Hutan, 2011)
Implementation reduced impact logging (RIL) technique in peatlands may contribute optimum and sustainable yield. A study was carried out at concession area of Kalimantan Subur Permai Company, West Kalimantan. The area war a natural peat swamp forest set aside for the land-clearing in preparation for the establishment of industrial plantation forest, in which consisted of miced barkwood trees. This study examined possibility of increasing productivy, decreasing logging cast, subsidence, and water fluctuation using RIL. technique. Results revealed that the use of RIL in felling, skidding, loading, un-loading, and banling at peat swamp forest could: 1. Increase productivity for each activity of consecutively 0,946 m²/hour, 2,449 m² / Бомт, 1,96 m²/bour, 1,871 m²/hour, and 2,158 ml/bour, 2. Decreased production cost of Rp 992,1/m², Rp 3.088,6/, Rp 127,9/m², Rp 99,7/m², and Rp 158,6/m² consecutively; 3. Inceased timber efficiency utilization (TUE) about 6% equal to Rp 74,400,000/year, 4. Subridence proceeded at 0.375 om/year rate, which corresponded to 1.875 cm in five years. This figure was still lower than that stipulated in the Indonesia's Government Decree (PP) Na. 150-2000. 4. The averages of water level at logging site and canal were 61.75 cm and 52.25 cm, respectively.